Development of a microplate duplex immunoassay to simplify detection of growth hormone doping: Proof of concept. Issue 4 (21st November 2021) - Marchand, Alexandre; Roy, Daisy; Monsheimer, Sarah A.; Lewis, Jennifer; Ericsson, Magnus
Abstract: The World Anti‐Doping Agency (WADA) prohibits athletes from using recombinant growth hormone (GH). The validated method used in antidoping laboratories for the direct detection of exogenous GH in serum requires two immunoluminometric assays (ILMAs): The first mainly measures the concentration of the full‐length (22 kDa) form of GH (recGH), and the second measures concentrations of multiple GH fragments produced by the pituitary gland (22 kDa, 20 kDa and other forms) (pitGH). The tube‐by‐tube analysis is laborious. A recent development opened new possibilities to simplify the detection of recGH in serum: multiplexed immunoassays that detect multiple targets in a single well of a 96‐well plate using an ELISA‐like procedure with high sensitivity. Our aim was to evaluate this technology by developing a customized assay for GH detection. One pair of antibodies with specificities similar to those of the recGH assay and one pair of antibodies compatible with pitGH detection were selected for a single duplex assay. Forty‐eight serum samples (negative athlete samples and positive samples following GH administration) were analyzed using the two methods. The microplate duplex assay discriminated between the negative athlete samples and the positive controls, although the rec/pit ratios from the duplex assay were lower than those obtained with the ILMAs. This new assay would offer a modern alternative to ILMAs, with fewer analytical steps and a smaller sample volume. However, an adaptation of the decision limits seems mandatory. Abstract : ‐ A recombinant GH and pituitary GH duplex immunoassay was developed‐ recGH and pitGH are detected conjointly in a single well of a 96‐well plate‐ Comparison was performed with WADA approved GH isoforms test ‐ Sera from GH administration and negative sera were well separated.